1994
DOI: 10.1007/bf02087705
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum iron and iron saturation without liver iron accumulation distinguish chronic hepatitis C from other chronic liver diseases

Abstract: One hundred twenty-three patients with chronic liver diseases of various etiologies were evaluated for their iron status. The patients were divided into four distinct groups: chronic hepatitis C (63), chronic hepatitis B (14), B + C (3) and nonviral chronic liver diseases (43). In 107 patients (87%) the chronic liver disease was confirmed by biopsy. Mean serum iron (+/- SD) levels in the above four groups were: 166 +/- 62, 103 +/- 52, 142 +/- 48, and 115 micrograms/dl; iron-binding capacity was 346 +/- 80, 325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 12 publications
2
38
0
7
Order By: Relevance
“…The relationship between HCV infection and serum levels of iron and ferritin was described soon after HCV was cloned. Later other investigators evaluated the association between iron levels in hepatic tissue and the severity of viral infection or the response to treatment with antiviral drugs (9,10). In our study, in which 95 samples of hepatic biopsy were analyzed, the presence of iron overload in hepatic tissue was observed in 31.6% of the cases.…”
mentioning
confidence: 77%
“…The relationship between HCV infection and serum levels of iron and ferritin was described soon after HCV was cloned. Later other investigators evaluated the association between iron levels in hepatic tissue and the severity of viral infection or the response to treatment with antiviral drugs (9,10). In our study, in which 95 samples of hepatic biopsy were analyzed, the presence of iron overload in hepatic tissue was observed in 31.6% of the cases.…”
mentioning
confidence: 77%
“…Chronic hepatitis C, with or without cirrhosis, often presents with abnormal iron indices [29,30] , particularly …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting, although not surprising, that subjects with persistently normal ALT have a significantly lower serum ferritin level because it has been reported that a high ferritin level is associated with more severe hepatitis and advanced liver disease. 23 Many HCV-positive patients with elevated aminotransferase activity have a serum ferritin level above the normal range, but only a minority of these patients have iron overload. 24 Two studies found a close relationship between serum ALT activity and ferritin level.…”
Section: Discussionmentioning
confidence: 99%